Time dependent fracture mechanics parameter for weldments - Plavšić, Mirko; Sedmak, Aleksandar (Journal of Production Engineering, 1994)
A path lnclendent integral expression has been introduced and proved to be valid time dependent fracture mechanics parameter for weldments. The integral expression comprises line integral, resembling C* integral, surface integral which takes into account for non-stationary problems, and another line integral, which takes into account for the weldment heterogeneity. In the case of a stationary problem surface integral vanishes, as does the additional line integral for a homogeneous material, reducing the integral expression to the C* integral. The complete integral expression has been calculated for a weld merit, using the finite element method.